PLA/LLDPE/Organo-Precipitated Calcium Carbonate Composites Containing LLDPE-g-OA Compatibilizers: Mechanical, Physical, Thermal, and Morphology - Ahmad Hafizullah Ritonga; Barita Aritonang; Gusliani Eka Putri; Khairiah Khairiah; Enzo Wiranta Battra Siahaan; Debi Meilani (Indonesian Journal of Chemistry, 2023)
A plastic composite consisting of polylactic acid (PLA), linear low-density polyethylene (LLDPE), oleic acid-grafted linear low-density polyethylene (LLDPE-g-OA) compatibilizer, and organo-precipitated calcium carbonate (O-PCC) have been successfully made in the molten state. This study aims to characterize the mechanical, physical, thermal, and morphological characteristics of the PLA/LLDPE/O-PCC plastic composite in the presence of an LLDPE-g-OA compatibilizer. The plastic composite was prepared by blending PLA, LLDPE, LLDPE-g-OA, and O-PCC using an internal mixer with a heating of 160 °C and a rotation of 100 rpm. LLDPE and LLDPE-g-OA are put together into the inner mixer chamber until melted, followed by PLA and O-PCC. The most optimum plastic composite composition is PLA/LLDPE/LLDPE-g-g-OA/O-PCC (67.5:22.5:5:5). The mechanical properties showed an increase in tensile strength of 9.78 MPa. The physical properties showed that the minimum water absorption was 0.74%, the biodegradation in humus soil showed a degradation rate of 0.09% per day, and the thermal properties showed better stability with a melting point of 146.5 °C. The FTIR spectrum is similar to the polymer blend without O-PCC. The morphology indicates that the composite is compatible and homogeneous. This semi-biodegradable plastic composite has significant implications for reducing the accumulation of plastic waste in the environment.